45th AIAA Aerospace Sciences Meeting and Exhibit 2007
DOI: 10.2514/6.2007-709
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dimensional Models for Control of Leading-Edge Vortices: Equilibria and Linearized Models

Abstract: When an airfoil is pitched up rapidly, a dynamic stall vortex forms at the leading edge and produces high transient lift before shedding and stall occur. The aim of this work is to develop low-dimensional models of the dynamics of these leading-edge vortices, which may be used to develop feedback laws to stabilize these vortices using closed-loop control, and maintain high lift. We first perform a numerical study of the two-dimensional incompressible flow past an airfoil at varying angles of attack, finding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…The change in the dynamics between the shaded (sub-critical) and unshaded (super-critical) regions can be viewed as an extension of the two-dimensional stability boundary. We claim that the change in the dynamics is attributed to a Hopf-bifurcation, as shown by Ahuja et al (2007) for the two-dimensional case. For lower aspect ratios, the vortex sheet emanating from the trailing edge forms and sheds hairpin vortices repeatedly.…”
Section: Flows At Higher Reynolds Numbermentioning
confidence: 99%
“…The change in the dynamics between the shaded (sub-critical) and unshaded (super-critical) regions can be viewed as an extension of the two-dimensional stability boundary. We claim that the change in the dynamics is attributed to a Hopf-bifurcation, as shown by Ahuja et al (2007) for the two-dimensional case. For lower aspect ratios, the vortex sheet emanating from the trailing edge forms and sheds hairpin vortices repeatedly.…”
Section: Flows At Higher Reynolds Numbermentioning
confidence: 99%
“…Then, the linear first-order set of equations with impulse input as the boundary condition should be solved for the flow variables u 1 , p 1 . Finally, the flow field with an arbitrary control input ε p can be estimated by Equation 17. The accuracy of the perturbation method will be investigated in Section 5.2.…”
Section: Zero-order Set Of Equations (Have Nominated As Equations A)mentioning
confidence: 99%
“…The simple model problem described here is part of a larger research program 3 that includes three-dimensional flow simulations, 4 experiments, 5 and reduced-order modeling. 6 Unsteady actuation has been used in the past for separation control. 7,8 Several studies have demonstrated that unsteady actuation near the separation point can reattach the flow, shorten the separation bubble, or suppress vortex shedding to reduce drag.…”
Section: Introductionmentioning
confidence: 99%